A proposed method for linear accelerator photon beam steering using EPID. (26th July 2018) - Barnes, Michael P.; Menk, Frederick W.; Lamichhane, Bishnu P.; Greer, Peter B.
Abstract: Beam steering is the process of calibrating the angle and translational position with which a linear accelerator's (linac's) electron beam strikes the x‐ray target with respect to the collimator rotation axis. The shape of the dose profile is highly dependent on accurate beam steering and is essential for ensuring correct delivery of the radiotherapy treatment plan. Traditional methods of beam steering utilize a scanning water tank phantom that makes the process user‐dependent. This study is the first to provide a methodology for both beam angle steering and beam translational position steering based on EPID imaging of the beam and does not require a phantom. Both the EPID‐based beam angle steering and beam translational steering methods described have been validated against IC Profiler measurement. Wide field symmetry agreement was found between the EPID and IC Profiler to within 0.06 ± 0.14% (1 SD) and 0.32 ± 0.11% (1 SD) for flattened and flattening‐filter‐free (FFF) beams, respectively. For a 1.1% change in symmetry measured by IC Profiler the EPID method agreed to within 0.23%. For beam translational position steering, the EPID method agreed with IC Profiler method to within 0.03 ± 0.05 mm (1 SD) at isocenter. The EPID‐based methods presented are quick to perform, simple, accurate and could easily be integrated with the linac, potentially via the MPC application. The methods have the potential to remove user variability and to standardize the process of beam steering throughout the radiotherapy community.